Ultrafast charge dynamics and photoluminescence in bilayer MoS2. (28th January 2021) - Ud Din, Naseem; Turkowski, Volodymyr; Rahman, Talat S
Abstract: Our examination of the interplay of ultrafast charge dynamics and electron–phonon interaction in the AA′ stacked bilayer MoS2 provides a microscopic basis for understanding the features (two peaks) in the emission spectrum. We demonstrate that while the initial accumulation of excited charge occurs at and near the Q point of the two-dimensional Brillioun zone, emission takes place predominantly through two pathways: direct charge recombination at the K point and indirect phonon-assisted recombination of electrons at the K valley and holes at the Γ hill of the Brillouin zone. Analysis of the wave vector dependencies of the electron–phonon interaction traces the higher energy peak to phonon-assisted relaxation of the excited electrons from the Q to the K valley in the conduction band. Our results thus reveal the importance of ultrafast charge dynamics in understanding photoemissive properties of a few-layer transition-metal dichalcogenide. These calculations are based on time dependent density functional theory in the density matrix formulation.